The preferred factors of accommodation among off-campus students / Nurul Hannan Nor Hizam - Nor Hizam, Nurul Hannan (2023)
Due to the economic growth during the pandemic that has slowly recovered, college demand is high because most of the students prefer to stay on campus, but the supply of hostel accommodation for the students is low. The ultimate aim of this research is to identify issues related to the housing accommodations among off-campus students. Therefore, the objectives of this research are to identify the preferred residential rental area among off-campus students, to determine the preferred factors of accommodation among off-campus students, and to rank the preferred factors of accommodation among off-campus students. The population for this study is 1,208 off-campus students at Universiti Teknologi MARA, Seri lskandar (UiTMSI). The sample size of this research is 292 respondents, which is needed for data collection by using random sampling. In order to answer the research question, the questionnaire has been distributed via Telegram and WhatsApp to off-campus students as primary data. Literature reviews that have already been conducted that are relevant to this topic serve as secondary sources of information. The data collection has been analysed using Descriptive Analysis in Statistical Package for the Social Sciences (SPSS) Version 28.0.